Eco-friendly Corrosion Inhibitor Coatings Based on Plant Waste Extracts: A Comparative Study of Tea Waste and Orange Peel - Filardli, Abdullah Malik Islam; Fadilah, Muhammad Zidan; Syahrizal, Muhammad Isyar; Rahmawati, Mafniatul; Febriani, Anisa Dwi; Adhilisty, Clarissa Mayla; Pratiwi, Latifah Indah; Salsabila, Ulfa Mazroatus; Setiawan, Naufal Dafa Akbar; Syahputra, Muhammad Rakha; Ghani, Afzaal Zaydan (Teknik Industri Universitas Ma Chung, 2025)
This study seeks to assess the efficacy of plant-based waste extracts, namely orange peel extract and tea waste extract, as natural corrosion inhibitors for mild steel submerged in a 3.5% NaCl solution. The methodology adhered to ASTM G31 standards, employing mild steel specimens coated with each extract using three application techniques: brushing, immersion, and spraying. The weight loss method was used to measure corrosion rates (Mmpy), enabling the calculation of inhibition efficiency (IE%) for each specimen. The uncoated control specimen consistently exhibited the highest corrosion rate (3.4523 Mmpy), categorized as